ChemInform Abstract: Confusing Quantitative Descriptions of Broensted—Lowry Acid—Base Equilibria in Chemistry Textbooks — A Critical Review and Clarifications for Chemical Educators. Issue 9 (4th March 2014) - Meister, Erich C.; Willeke, Martin; Angst, Werner; Togni, Antonio; Walde, Peter
Abstract Review: 28 refs.